2008
DOI: 10.1038/nsmb.1468
|View full text |Cite
|
Sign up to set email alerts
|

The Nrd1–Nab3–Sen1 termination complex interacts with the Ser5-phosphorylated RNA polymerase II C-terminal domain

Abstract: RNA polymerase II (Pol II) in Saccharomyces cerevisiae can terminate transcription via several pathways. To study how a mechanism is chosen, we analyzed recruitment of Nrd1, which cooperates with Nab3 and Sen1 to terminate small nucleolar RNAs and other short RNAs. Budding yeast contains three C-terminal domain (CTD) interaction domain (CID) proteins, which bind the CTD of the Pol II largest subunit. Rtt103 and Pcf11 act in mRNA termination, and both preferentially interact with CTD phosphorylated at Ser2. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
347
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(374 citation statements)
references
References 61 publications
20
347
1
Order By: Relevance
“…The NNS complex role in NCR may represent part of this pathway intersection. Nrd1 preferentially interacts with Ser5-phosphorylated CTD (21,22). Nrd1 and Nab3 binding to NCR transcripts could normally act together with the appropriate GATA factors to attenuate expression of genes involved in the use of nonpreferred nitrogen sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NNS complex role in NCR may represent part of this pathway intersection. Nrd1 preferentially interacts with Ser5-phosphorylated CTD (21,22). Nrd1 and Nab3 binding to NCR transcripts could normally act together with the appropriate GATA factors to attenuate expression of genes involved in the use of nonpreferred nitrogen sources.…”
Section: Discussionmentioning
confidence: 99%
“…NNS interacts with Pol II in part through binding of Nrd1 to phosphorylated Ser5 on the C-terminal domain (CTD) (21)(22)(23), a pattern of CTD phosphorylation most prominent in the early stages of the transcription cycle, limiting NNS termination to promoter-proximal transcripts (24)(25)(26)(27)(28)(29). The NNS complex also interacts with the TRAMP (Trf4/Trf5-Air1/Air2-Mtr4 polyadenylation) complex to couple termination to processing by the nuclear exosome (30)(31)(32)(33).…”
mentioning
confidence: 99%
“…The studies of Gudipati et al (2008) and Vasiljeva et al (2008a) provide an explanation of why termination depends on the distance traveled by RNAPII, and how RNAPII chooses between the 39 cleavage and polyadenylation pathway for mRNA termination and the Nrd1 complex for noncoding RNAs, short ORFs and CUT termination. Short transcripts are mostly associated with Ser5 phosphorylation, which recruits the Nrd1 complex.…”
Section: A Wider Role For the Nrd1 Complex In Gene Expressionmentioning
confidence: 99%
“…They also showed that binding of Nrd1 to the nascent transcript, even if not sufficient, is necessary for efficient termination. Accordingly, Vasiljeva et al (2008a) showed that Nrd1 has a high affinity for the CTD phosphorylated at Ser5 and Ser5/Ser2. Additionally, association of Nrd1 with a snoRNA or mRNA gene is not affected by inhibition of Ser2 phosphorylation.…”
Section: A Wider Role For the Nrd1 Complex In Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation